Alzheimer task identification based on stimulus-response compatibility for digital kitchen environment - Nur Waheeda Basharudin (School of Computer and Communication Engineering, 2019)
As being previously explained, kitchen is one of room in the house where it involved variety of activities such as preparing food, storing provisions, doing laundry and others. These scenario can be contribute to dangerous accident occurs in the kitchen especially to elderly with Alzheimer's disease such as burning the food, forget to turn off switches of electric appliances and scalded by hot water if proper monitoring is not being done. Thus, this thesis focusing in developing an ambient assisted living of kitchen environment by applying ambient intelligence technology. Targeted subjects for this thesis are Alzheimer's patients who live alone at home while caregivers are not around with them. The purpose of this design is to let the patients living independently with the assisting of ambient intelligence technologies. It is expected that by implementing these technologies in the kitchen, it can minimize the burden carry by caregiver to take care of Alzheimer's patients 24 hours in a day.